Hiding in plain sight’: exploring the complexity of sexual safety within an acute mental health setting - McGarry, Julie (Wiley, 2018)
It is increasingly being recognised that individuals who access acute mental health services are at risk of sexual assault. Assaults may be perpetrated by other patients but also by staff working in mental health environments, although this latter group remain largely under researched. Following a reported professional sexual assault and review of an acute in-patient mental health setting in the UK, the overall aim of the present study was to explore the mechanisms and structures that were put into place following the investigation and in so doing examine the wider questions of sexual safety in acute mental health settings. A qualitative approach was utilised and involved interviews with clinical staff (n=8). Thematic analysis was used to analyse the data resulting in four main themes: ‘Feeling betrayed’: The relational context of the ward environment’; ‘Doing what we were meant to be doing’: Quality of leadership’; ‘Covering yourself’: Safeguarding practice; ‘The subtleties of abuse’: Complexities of safeguarding’. The findings of the study highlights the need for clear organisational structures of support, a clearer understanding of ‘sexual safety’ and education and training which explicitly addresses recognition and complexity of sexual violence.